2017
DOI: 10.1016/j.atherosclerosis.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Race/ethnic and sex disparities in the non-alcoholic fatty liver disease-abdominal aortic calcification association: The Multi-Ethnic Study of Atherosclerosis

Abstract: Background and aims This study investigated the associations of non-alcoholic fatty liver disease (NAFLD) and abdominal aortic calcification (AAC) volume and density, and whether these relationships vary by race/ethnicity and/or sex, information that are limited in current literature. Methods We studied 1,004 adults from the Multi-Ethnic Study of Atherosclerosis to assess the relationship between NAFLD (liver-to-spleen ratio <1) and the following measures of AAC: presence (volume score >0, using Poisson regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…110 Most of the studies reviewed utilized primary data collection done by the Third National Health and Nutrition Examination Survey (1988)(1989)(1990)(1991)(1992)(1993)(1994), or MESA (2002)(2003)(2004)(2005), which may produce outdated results. 2,50,51,84,86,111 Prevalence of NAFLD, thus, in current, prospective population-based studies, may be higher.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…110 Most of the studies reviewed utilized primary data collection done by the Third National Health and Nutrition Examination Survey (1988)(1989)(1990)(1991)(1992)(1993)(1994), or MESA (2002)(2003)(2004)(2005), which may produce outdated results. 2,50,51,84,86,111 Prevalence of NAFLD, thus, in current, prospective population-based studies, may be higher.…”
Section: Resultsmentioning
confidence: 93%
“…However, only a few studies compare this cohort with patients from a Caucasian, Hispanic, or African origin. 44,50,51 Diabetes, Metabolic Syndrome and Obesity: Targets and Therapy downloaded from https://www.dovepress.com/ by 44.224.250…”
Section: Afro-caribbean Ethnic Groupmentioning
confidence: 99%
“…The association between NAFLD and AAC may differ between ethnic groups. In a Multi-Ethnic Study of Atherosclerosis (MESA), NAFLD was signi cantly associated with the prevalence of AAC in African Americans but was not signi cantly associated with the prevalences in Caucasians, Asians, or Hispanics [25]. A cohort study of African Americans also showed that NAFLD was independently correlated with AAC [26].…”
Section: Discussionmentioning
confidence: 99%
“…Using these ROIs, HU attenuation were calculated for liver and spleen. As in previous work from MESA [16,17], NAFLD was defined as L/S ratio <1.0. The L/S ratio was calculated by taking mean attenuation values of both right liver lobe ROIs and dividing it by the spleen's attenuation value [18].…”
Section: Nafld Assessmentmentioning
confidence: 99%